2005
DOI: 10.1590/s0004-282x2005000500031
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da condução nervosa motora na doença de McArdle: relato de caso

Abstract: RESUMO -A doença de McArdle (glicogenose tipo V) é miopatia metabólica com sintomas de intolerância ao exercício, causados pela deficiência da enzima miofosforilase. Nesses pacientes, o estudo da condução n e rvosa motora após período de esforço muscular máximo ou ao estímulo repetitivo pode revelar achados característicos da doença. Descrevemos o caso de um homem de 37 anos com sintomas de intolerância aos e x e rcícios, fadiga muscular e cãibras no início da atividade física com a presença do fenômeno de "se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The disease manifestations vary from muscle fatigue, cramps, contracture and intolerance to exercise [24], [20] to more severe conditions, such as myoglobinuria (the presence of myoglobin in the urine, making it darker) and rhabdomyolysis (the breakdown of muscle tissue that leads to the release of muscle fiber contents into blood [31]. The action potential is also affected in patients with MS. Lorenzoni et al [32] reported one case of MS in which needle electromyography showed a reduction of the compound muscle action potential amplitude following a short period of voluntary muscle activity or high-frequency repetitive stimulation. Those findings may have been observed due to absence of glycogen, which normally serves as an energy substrate for the active transport of ions through the neuronal membrane.…”
Section: Mcardle Syndromementioning
confidence: 99%
See 3 more Smart Citations
“…The disease manifestations vary from muscle fatigue, cramps, contracture and intolerance to exercise [24], [20] to more severe conditions, such as myoglobinuria (the presence of myoglobin in the urine, making it darker) and rhabdomyolysis (the breakdown of muscle tissue that leads to the release of muscle fiber contents into blood [31]. The action potential is also affected in patients with MS. Lorenzoni et al [32] reported one case of MS in which needle electromyography showed a reduction of the compound muscle action potential amplitude following a short period of voluntary muscle activity or high-frequency repetitive stimulation. Those findings may have been observed due to absence of glycogen, which normally serves as an energy substrate for the active transport of ions through the neuronal membrane.…”
Section: Mcardle Syndromementioning
confidence: 99%
“…When clinical complaints are indicative of disease presence, diagnostic testing must be performed. One of the methods used to investigate the presence of MS is histochemical analysis of the muscle tissue, which may detect the subsarcolemmal accumulation of glycogen [20], [32], as was found in several cases. Such an accumulation may be due to excess glycogen that cannot be broken down.…”
Section: Implications For the Musclesmentioning
confidence: 99%
See 2 more Smart Citations